Human Skeletal Muscle Disuse Atrophy: Effects on Muscle Protein Synthesis, Breakdown, and Insulin Resistance—A Qualitative Review - Rudrappa, Supreeth S.; Wilkinson, Daniel J.; Greenhaff, Paul L.; Smith, Kenneth; Idris, Iskandar; Atherton, Philip J. (Frontiers in Physiology, 2016)
The ever increasing burden of an ageing population and pandemic of metabolic syndrome worldwide demands further understanding of the modifiable risk factors in reducing disability and morbidity associated with these conditions. Disuse skeletal muscle atrophy (sometimes referred to as “simple” atrophy) and insulin resistance are ‘non-pathological’ events resulting from sedentary behaviour and periods of enforced immobilization e.g. due to fractures or elective orthopaedic surgery. Yet, the processes and drivers regulating disuse atrophy and insulin resistance and the associated molecular events remain unclear – especially in humans. The aim of this review is to present current knowledge of relationships between muscle protein turnover, insulin resistance and muscle atrophy during disuse, principally in humans. Immobilisation lowers fasted state muscle protein synthesis (MPS) and induces fed-state ‘anabolic resistance’. While a lack of dynamic measurements of muscle protein breakdown (MPB) precludes defining a definitive role for MPB in disuse atrophy, some proteolytic “marker” studies (e.g. MPB genes) suggest a potential early elevation. Immobilisation also induces muscle insulin resistance (IR). Moreover, the trajectory of muscle atrophy appears to be accelerated in persistent IR states (e.g. Type II diabetes), suggesting IR may contribute to muscle disuse atrophy under these conditions. Nonetheless, the role of differences in insulin sensitivity across distinct muscle groups and its effects on rates of atrophy remains unclear. Multifaceted time-course studies into the collective role of insulin resistance and muscle protein turnover in the setting of disuse muscle atrophy, in humans, are needed to facilitate the development of appropriate countermeasures and efficacious rehabilitation protocols.